Current Study Concerning Parental Authority to Educate Children Reviewed Against the Provisions of the Child Protection Law in the Modern Era - Taufan Zakaria; Faisal Santiago (International Journal Labs, 2023)
This research examines the current authority of parents in educating children, with a focus on the provisions of the Child Protection Law in the modern era. The research method was carried out through text analysis and literature studies related to legal provisions relating to the role of parents in educating children. At the discussion stage, the research identified the dynamics of parental authority involving aspects of children's freedom, human rights, and socio-cultural changes in the modern era. This study examines the concepts of appropriateness and relevance of the provisions of the Child Protection Law in accommodating the needs and rights of children to receive a balanced and quality education. Article 1 paragraph (1) of the Child Protection Law (No. 35 of 2014) states that children have the right to protection, care, and self-development so that they can live, grow, and develop optimally. The research results show that a deep understanding of these articles is crucial for maintaining a balance between children's rights and parental authority in the dynamic modern era. This research contributes to legal and educational literature, by presenting the latest views regarding the role of parents in educating children amidst the changing dynamics of modern society. Practical implications include recommendations for improving understanding and implementation of legal provisions, as well as educational approaches that support children's participation in their educational process.